Epidemiological factors associated with colorectal cancer in north-east India: A hospital-based descriptive cross-sectional study - Ralte, Zothansanga; Paleti, Venu Gopala Reddy; Kumar, Vimal (Journal of Surgery and Medicine, 2021)
Background/Aim: Identifying the epidemiological factors associated with the causation and development of colorectal cancer may help gain a better understanding of the disease to assist in screening and assessing the prognosis. This study aimed to determine and analyze the clinical-epidemiological profile of colorectal cancer. Methods: A cross-sectional study was conducted at a tertiary teaching hospital on 138 colorectal cancer patients for 1.6 years (June 2017 to December 2018). The participants were examined clinically, and detailed history regarding demographic features, adverse habits, occupation, and family history was taken using a structured pro forma. The tumor stage and site of cancer were considered the primary outcomes. Descriptive and inferential analyses were carried out using coGuide software, V.1.03, and the P-value was set at <0.05. Results: The mean age was 54.52 (15.9) years, and 86 (62.30%) patients were males. Twenty-seven (19.60%) had hypertension, 20 (14.50%) had fissures piles and 17 (12.30%) had Diabetes Mellitus. Ninety-seven (70.28%) had a history of smoking and alcohol consumption. Carcinoma cases were more common among patients with a history of non-vegetarian dietary intake, but it was not statistically significant. In our study, smoking and comorbidities like (hypertension, fissure piles) proved to be associated with stages of tumor (P<0.05). Conclusion: The associated risk factors in our study were age >50 years, smoking, and hypertension. If controlled, these can help reduce the overall incidence of CRC in the Indian population.